A numerical procedure for shot peening optimisation by means of non-dimensional factors. (1st January 2000) - Baragetti, S.; Guagliano, M.; Vergani, L.
Shot peening is widely used to improve the fatigue behaviour of mechanical components. The improved performances of shot peened components are generally put into relation with the residual stress field induced. The aim of the present paper is to define a calculation approach, based on FE analyses, able to predict, once the shot peening parameters are known, the residual stress profile. In this way, it is possible to optimise the results of shot peening by taking into account the applied loads. The possible application of a non-dimensional number to summarise the shot peening conditions was evaluated. It was also possible to express non-dimensional residual stress profiles (residual stresses/yield stress of the material) as a function of this non-dimensional number. The measurements carried out on shot peened specimens by means of a X-ray diffractometer allowed for critical analyses of the results.